Exploring home-to-school trip mode choices in Kandy, Sri Lanka - Charitha Dias (12191671) (2022)
Schools are major trip generators in urban areas and school trips may largely contribute to the congestion, particularly during morning peak hours. This study investigates the home-to-school trip mode choices in Kandy city, which is a major city in Sri Lanka. The data were collected through a questionnaire survey distributed among junior, lower senior, and upper senior students of ten major schools located in Kandy city in 2015. School trip mode choices, that comprise several common travel modes in Sri Lanka, i.e., walking, public bus, school bus, school van, private vehicles (car or van), motorcycle, and three-wheeler, were modeled using multinomial logit and mixed logit frameworks. The results indicated that gender, age, household income, school type and distance play a significant role in determining the school transport mode. That is, male students were more likely to choose public buses, walking, and private vehicles relative to other transport (three-wheeler and motorcycle combined) as compared to female students. Further, older students were more likely to walk, take a school bus and public bus relative to other transport when compared to the younger students. Distance to school was found to significantly affect all the school transport modes. National or Provincial school students were more likely to use a school bus and less likely to use a private vehicle. Transport planners and policymakers could use the outcomes of this study, especially to implement congestion mitigation measures in city centers during morning peaks. Besides, some aspects of this study could be used to regulate and legalize some private transport modes, e.g., privately operated school vans, to provide a safer, reliable, and economical service to school-going children. Other Information Published in: Journal of Transport Geography License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jtrangeo.2022.103279